LAXATIVE EFFECT OF GREEN GEDI LEAVES INFUSES (Abelmoschus manihot (L.) Medik) ON MALE WHITE MICE (Mus musculus) - Birgitta Vania Rarasati (Universitas Syiah Kuala, 2019)
Abstract. Background: Gedi plant (Abelmoschus manihot (L.) Medik) of the Malvaceae family is a plant which leaf is used by peoples for the treatment of several illnesses such as constipation. Purpose: To investigate the laxative activity of green gedi leaves infuses (Abelmoschus manihot (L.) Medik) on male white mice.Method: This study is an experimental study. Mice were divided in 5 groups of 6 animals each, first group as negative control (CMC Na 0.5%) while group 2, 3 and 4 were treated with green gedi leaves infuses (Abelmoschus manihot (L.) Medik) at doses of 130, 260 and 520 mg/kgBW, per as respectively and group 5 as positive control (bisacodyl). The laxative activity was determined based on the frequency of defecation, weight of feces and consistency of feces.Results: It is found that 520 mg/kgBW dose has the highest mean of defecating frequency (7.17) and 260 mg/kgBW dose has the highest mean of feces weight (0.20). Statically however, there is no significant difference between the groups overall with p value of 0.132 and 0.246 for defecating frequency and feces weight respectively. There is no difference between the groups in term of feces consistency with both not defecating and hard feces.Conclusion: The research concludes that there is no significant laxative activity between each groups after administration of several dosages in 6 hours on mice thus the use of green gedi leaves as laxative in society can not be proven empirically in the laboratory.Keywords: gedi leaf, Abelmoschus manihot (L.) Medik, laxative effect, constipation